Sedimentology of the mid-Carboniferous fill of the Olta paleovalley, eastern Paganzo Basin, Argentina: Implications for glaciation and controls on diachronous deglaciation in western Gondwana during the late Paleozoic Ice Age - Moxness, Levi D.; Isbell, John L.; Pauls, Kathryn N.; Limarino, Carlos Oscar; Schencman, Laura Jazmín (Journal of South American Earth Sciences)
Both global and regional climate drivers contributed to glaciation during the late Paleozoic Ice Age (LPIA). However, the transition from icehouse to greenhouse conditions was asynchronous across Gondwana suggesting that, in some cases, regional controls played a significant role in deglaciation. Of particular interest to understanding changing LPIA climatic conditions, is the eastern Paganzo Basin. This region was flanked by ice centers in the Precordilleran and Sierras Pampeanas regions of Argentina on the west, and major ice sheets in the Paraná, Chaco-Paraná, and Sauce Grande basins to the east, all of which resided between ∼40 and 65° S latitude. Hypotheses on the occurrence of ice in the eastern Paganzo Basin are based on interpretations of the narrow, steep-walled, Olta-Malanzán paleovalley as carved by an alpine glacier or by an outlet glacier draining an eastern ice sheet, and that glaciers deposited coarse clastics within the paleovalley. However, we found no evidence for glaciation. Rather, gravel from prograding alluvial fans/fan deltas and rock falls ponded drainage resulting in lacustrine activity in the eastern end of the valley. A transition from either subaerially or shallow subaqueously deposited sandstones to marine mudstones in the western end of the Olta paleovalley suggest a marine transgression, which, in turn, was overlain by deposits of prograding Gilbert-type deltas. Dropstones were from rock falls off valley walls and rafting by lake ice rather than from icebergs. Therefore, we conclude that the climate in western Argentina resulted from uplift induced glaciation in the Precordilleran region and along the western margin of the Paganzo Basin, and the occurrence of a precipitation shadow to the east. The disappearance of the western glaciers during the mid-Carboniferous, prior to deglaciation elsewhere at the same paleolatitude, resulted from a westward shift in the position of the active margin, collapse of the glaciated upland(s), and an expansion of the precipitation shadow across the ...